THE LEGALITY OF TRADITIONAL OIL MINING EXPLORATION IN RANTO PEUREULAK, EAST ACEH: AN ANALYSIS OF THE ISLAMIC ECONOMIC LAW PERSPECTIVE - Muhammad Khaidir; Ajidar Matsyah; Muhammad Dayyan (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This article aims to examine the legality of oil mining resulting from traditional mining exploitation by the Ranto Pereulak community, East Aceh. This research uses descriptive qualitative research methods and the approach used in this research is a sociological normative approach. This research was located in Ranto Peureulak District, which is one of the sub-districts in East Aceh Regency. The results of this research show that the East Aceh Government through Qanun Number 6 of 2009 provides space for the community to manage mining products, in this case oil, by obtaining an IUP issued by the East Aceh government and going through all the conditions therein. The IUP is granted by the Regent after obtaining principle permission or approval from the Governor through the relevant provincial and district level agencies. However, in practice, many people in Ranto Peureulak District, East Aceh Regency, in managing illegal wells traditionally do not follow the applicable SOPs or regulations. Then the oil drilling carried out can endanger the health of workers and the surrounding community. This can also have an impact on the environment, because it does not pay attention to health standards or Health Safety and Environment or abbreviated as (HSE), which is the main priority for mining. In terms of safety too, it often catches fire and causes casualties, both workers and residents. Because drilling oil and gas wells is a very complex process and at each step procedures, requirements and important decisions are required that must be considered and implemented very carefully.